Phân tích các nhân tố tác động đến ý định phân loại rác thải của du khách tại điểm đến Đà Nẵng: Nghiên cứu đa văn hoá - Đặng Thị Thu, Trang; Cao Huệ , Mẫn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to analyze the factors affecting tourists’ intention to waste sorting at Da Nang destination, using the theory of planned behavior (TPB) combined with the MOA model (Motivation-Opportunity-Ability). After analyzing data from 440 tourists visiting Da Nang using PLS-SEM, the results show that attitude, subjective norms, perceived behavioral control, motivation and ability all have direct and positive impacts on tourists’ intention to waste sorting. Additionally, the study also confirms the important mediating role of attitude and also shows that the impact of perceived behavioral control on attitudes was stronger among European tourists than among Vietnamese tourists. From this result, the study proposed recommendations for tourism authorities and tourism businesses to improve social and personal factors to promote tourists’ waste sorting behavior.